Buya Hamka's Thoughts on Religious Moderation in The Political Context - R.M. Fakhri Ali Akbar; Ainur Ropik; Ibrahim Mifthafariz Mirza (Universitas Islam Negeri Raden Fatah Palembang, 2024)
This research aims to examine Buya Hamka's thoughts on religious moderation in the political context based on his works. This study adopts a qualitative approach, utilizing the literature review research type and employing content analysis as the research method. The data source consists of Buya Hamka's works related to religious moderation. The research focuses on the ideas presented by Buya Hamka within his works. The theoretical framework used is the moderation thinking theory of Muhammad Quraish Shihab, which comprises three pillars of moderation. The first pillar is Justice. Buya Hamka really emphasizes the importance of being fair to everyone, which is reflected in his attitude regarding human rights among fellow citizens which must be upheld. The second pillar is Balance, advocating democracy in Islam which considers balance without discriminating against any group or religious view, this is demonstrated by a neutral attitude without taking sides with one particular group. The third pillar is Tolerance which guarantees coexistence between religious communities without weakening their beliefs, in order to encourage unity and harmony between citizens in Indonesia.